Working Motivation of Multi-Generational Workforce in Vietnam - Nguyen, Quynh Mai (2018)
Motivated workers are the key to the success of an organization. In the context where there are different generations of employees working together at the same time, it is necessary for managers to understand the motivational forces of each generation to improve business performance. The aim of this study is to investigate on motivation factors influencing generational workforce of Vietnam and the potential effect of generational identification on these factors. The research focused on three generations of Vietnam workforce, including the Baby Boomers, Generation Y, and Generation Z, which had been re-categorized due to specific characteristics of Vietnam social background. The study employed the qualitative semi-structured interview based on Herzberg’s motivation model (1959) to understand the perspectives of sixteen employees in these three generations. Despite the limitations of using cross-sectional data and generalizability, the study presented the differences in the motivation of three generations: While Baby Boomers were motivated by Recognition and required Job Security and Salary, Generation Y cared more about Work-Life Balance, and Generation Z was willing to sacrifice de-motivational factors at the beginning of their career. All three generations were positively influenced by Personal Growth, and the younger paid more attention to the Nature of their work than older generations. The study suggested these differences should be better explained by age and career stage rather than generational identities.